The Role of Islamic Religious Education Teachers in Nurturing Religious Character of Third-Grade Students at SDN 2 Donotirto, Kretek, Bantul - Darmawan Adi Putra; Radino Radino (Universitas Muhammadiyah Enrekang, 2024)
Character education is seen as important and one of the starting points for building a national civilization. Character education has actually been around since the existence of education because, in general, education basically aims to develop good character. The number of bad characters appearing on the surface is a national concern. The method in this research is qualitative with a descriptive approach. The results of this research show that the role of a PAI teacher includes several roles. A PAI teacher, like other teachers, has a very important role, such as teacher, guide, role model, coach, advisor, counselor, and facilitator, which is in line with the current curriculum and carries out evaluations. The role of PAI teachers in developing the religious character of class III students at SDN 2 Donotirto is carried out using several methods, namely the exemplary method, advice, habituation, reward and punishment, and the story method. In this exemplary method, all madrasah members are involved in providing good role models and can be good examples for students in terms of speaking, worship, dressing, time discipline, and even respecting other people. The advice method is carried out by all teachers at school, whether it is typing lessons, flag ceremonies, or before the Dhuha and Asmaul Husna prayers.